Comparative study of surface roughness between electropolishing process and traditional sanding for low carbon steel - Eduardo Schmitzhaus, Tobias; Do Nascimento Ângelo Cristaldo, Matheus; Cristiano Schmitzhaus, Wagner (International Journal of Scientific World, 2024)
Steel is a versatile material utilized across various sectors, encompassing both industrial and decorative applications. AISI (American Iron and Steel Institute) 1005 steel, recognized for its low carbon content (approximately 0.05% carbon), is commonly referred to as mild steel and finds extensive use in society. This study aims to investigate the influence of electropolishing parameters, specifically current density, and time, on the surface roughness of steel. The methodology involved the preparation of samples for electropolishing tests, systematic variation of the parameters, and subsequent analysis of the resulting surface finish through roughness measurements. Samples subjected to higher current densities for shorter durations exhibited substantial reductions in roughness, while longer durations resulted in minimal or negligible changes in roughness regardless of the current density employed. This comparative analysis between electropolishing and tradi-tional sanding techniques provides valuable insights into optimizing surface finishing processes for low carbon steel applications.